Respuesta :

Answer:

C

Explanation:

Given :

⇒ 2x + 5y = -13 [Equation 1]

⇒ 4x - 3y = 13 [Equation 2]

===========================================================

Multiply the 1st Equation by 2 :

⇒ 2 × (2x + 5y) = 2 × -13

⇒ 4x + 10y = -26 [Equation 3]

===========================================================

Subtract : Equation 2 - Equation 3

⇒ 4x - 3y - 4x - 10y = 13 - (-26)

⇒ -13y = 39

⇒ y = -3

Answer is -3

Multiple equation 1 by -2
-4x-10y=26

Add it to the second equation to cancel out the x terms

-4x-10y=26
+4x-3y=13

-13y =39
Y = -3